Evaluation of triticale genotypes for terminal drought tolerance using physiological traits - AKBARIAN, ABOULGHASEM; ARZANI, AHMAD; SALEHI, MARYAM; SALEHI, MINA (The Indian Journal of Agricultural Sciences, 2026)
Drought is a major constraint to crop production worldwide. The effect of terminal drought stress on the physiological traits of 18 triticale (X. triticosecale) lines comprising nine doubled haploid (DH) and nine corresponding advanced lines (F7-8) and two bread wheat cultivars (control) was investigated under field conditions during two growing seasons of 2007–09. Plants were grown under full irrigation until the mid-jointing stage when drought stress was applied to the plant. Chlorophyll content, carotenoids content, proline content, relative water content (RWC), flag leaf area, flag leaf angle and grain yield were assessed. Triticale lines performed superior than wheat cultivars for drought tolerance considering both grain yield and majority of physiological traits. Grain yield positively and significantly correlated with the ratio of total chlorophyll (a+b) to total carotenoid and RWC under both environmental conditions. DH line number 4 possessed the greatest values of RWC, chlorophyll a, chlorophyll b, chlorophyll a+b and ratio of total chlorophyll (a+b) to total carotenoid under drought stress conditions. These accompanied by having high proline content and low grain yield reduction due to drought stress was ranked this DH line as superior drought tolerant genotype. The results revealed an inverse and significant relationship between grain yield loss due to drought stress with proline content under drought stress (r = -0.61**), provided an evidence supporting the role of proline in drought tolerance.